Internalisasi Nilai-nilai Karakter Religius dan Gotong Royong Siswa melalui Ekstrakurikuler Rohis di SMK-SPP Negeri 3 Kerinci - Mukhlis; Gusril Kenedi; Nursyamsi; Pefriadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The undeniable reality of moral decay, particularly among adolescents, seems to persist in the era of scientific and technological advancements, especially within the middle school student population. Therefore, the role of schools extends beyond being institutions solely for acquiring knowledge; they should also be capable of providing education that fosters character development. In an effort to internalize character education values, this school has introduced the extracurricular activity called